2015
DOI: 10.1073/pnas.1512243112
|View full text |Cite
|
Sign up to set email alerts
|

Selective optogenetic activation of arcuate kisspeptin neurons generates pulsatile luteinizing hormone secretion

Abstract: Normal reproductive functioning in mammals depends upon gonadotropin-releasing hormone (GnRH) neurons generating a pulsatile pattern of gonadotropin secretion. The neural mechanism underlying the episodic release of GnRH is not known, although recent studies have suggested that the kisspeptin neurons located in the arcuate nucleus (ARN) may be involved. In the present experiments we expressed channelrhodopsin (ChR2) in the ARN kisspeptin population to test directly whether synchronous activation of these neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
113
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 51 publications
6
113
1
2
Order By: Relevance
“…Kisspeptin is a potent and critical regulator of GnRH neurons [41] , and there is an ongoing hypothesis that the ARN kisspeptin population is involved in mediating gonadal steroid hormone negative feedback to GnRH neurons [42] . While there is no question that ARN kisspeptin neurons are involved in driving GnRH/LH release [43] , the present data suggest that ARN kisspeptin neurons are almost entirely distinct from the previously reported ARN GABA neurons that send dense, plastic projections to the GnRH neuron cell bodies [15] . This is in line with evidence demonstrating that ARN kisspeptin neurons do not project to GnRH neuron cell bodies in the rostral forebrain, and are more likely to regulate GnRH neurons at dendronic or terminal levels [44] .…”
Section: Discussioncontrasting
confidence: 60%
“…Kisspeptin is a potent and critical regulator of GnRH neurons [41] , and there is an ongoing hypothesis that the ARN kisspeptin population is involved in mediating gonadal steroid hormone negative feedback to GnRH neurons [42] . While there is no question that ARN kisspeptin neurons are involved in driving GnRH/LH release [43] , the present data suggest that ARN kisspeptin neurons are almost entirely distinct from the previously reported ARN GABA neurons that send dense, plastic projections to the GnRH neuron cell bodies [15] . This is in line with evidence demonstrating that ARN kisspeptin neurons do not project to GnRH neuron cell bodies in the rostral forebrain, and are more likely to regulate GnRH neurons at dendronic or terminal levels [44] .…”
Section: Discussioncontrasting
confidence: 60%
“…In females, low or depleted estrogen levels evoke transcriptional activation of Kiss1 ARH neurons (7)(8)(9), and stimulation of genetically defined Kiss1 ARH neurons in vivo is sufficient to evoke gonadotropin release (10). During starvation, gonadal steroid levels plummet, yet Kiss1 ARH neurons are unable to drive gonadotropin release.…”
mentioning
confidence: 99%
“…Immunofluorescence was undertaken as reported previously (24). Coronal brain sections (30 μm thick) covering the full length of the ARN were used to determine the locations of optic fibers and/or processed for dual-label analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that optogenetic activation of ARN KISS neurons for >2 min at 10 Hz generates pulse-like increments in LH secretion in anesthetized mice (24). However, the fiber photometry studies above clearly demonstrate that ARN KISS neuron calcium events last for only ∼1 min.…”
Section: Significancementioning
confidence: 91%
See 1 more Smart Citation